Dissecting Indonesian Teacher Ethics Code on Disciplinary Penalties - Enjelie; Lukas; Sefle, Yohana; Krimadi, Ortison; Wenda, Daton (Balai Diklat Keagamaan Papua, 2023)
Abstract The issue in these studies shows that there were negative impulses on the term discipline, sanctions that often lead to students. However, the term punishment itself does not only target rule breakers. However, there are other factors besides students, namely the system, culture, economy, the existence of domestic violence which has an impact on the psychology of students through SD 2 Kereng Bangkirai and SMP Negeri 3 Rungan, Central Kalimantan. Furthermore, researchers aim to show a variety of narratives as voices that do not need to be ignored by readers or systems that embrace the silencing of voiceless voices. Methods of this research are qualitative research methods with direct interview techniques as primary narrative income from teachers as research subjects. Results show that there is an action of sanctioning students as a deterrent effect but there are also narratives that view punishment as an additional job for violators.